Lacto S.A. – caso práctico - Quispe Francia, Kevin Iván (2019)
The objective of this work of professional sufficiency is to estimate the best price to sell the shares of Lacto S.A. making the valuation of the company under the discounted cash flow method, analyzing the financial information of the company and data extracted from other secondary sources. To comply with this, the projection of financial statements was carried out, based mainly on the historical information presented from 2017 and 2018, to subsequently estimate free cash flows, in a reliable projection horizon until considering that the growth of the Company be stable and reasonable. Likewise, we carried out different analyzes to evaluate the performance of the company in the Peruvian dairy industry, and it was also evaluated in what way the application of the new standards that come into force would impact the valuation of Lacto. Finally, the sensitivity analysis will be performed and simulate different scenarios to estimate a range of value to put the actions of Lacto S.A. on sale.